GRAMMATICAL METAPHOR REPRESENTATIONS IN NEWS ITEM TEXT OF JAKARTA POST - Winda Syafitri (UNIB Press, 2021)
This article aims to investigate grammatical metaphor representation in news item text of Jakarta Post. This research was conducted by applying a descriptive research design. The data were taken from a news item text from Jakarta Post entitled “BREAKING: 189 people on downed Lion Air flight, ministry says.” This article was published on October 29, 2018 in Jakarta Post sites. This text was then analyzed by coding the lexical representation as congruent and incongruent ones. From a news item text Jakarta Post, the finding is Representation of incongruent coding is only 17% of the text; the rest (83%) is congruent coding. Grammatical Metaphors representation in the text is dominated by the changes of verbs becoming nouns around 71%.